Chemical stability and degradation mechanism of Mg3Sb2-xBix thermoelectrics towards room-temperature applications. (15th October 2022) - Li, Airan; Nan, Pengfei; Wang, Yuechu; Gao, Ziheng; Zhang, Shiyun; Han, Zhongkang; Zhao, Xinbing; Ge, Binghui; Fu, Chenguang; Zhu, Tiejun
Abstract: Mg3 Sb2- x Bi x compounds have recently attracted surging research attention owing to their low cost and high thermoelectric performance that is comparable with the commercialized Bi2 Te3- x Se x alloys. For practical applications, chemical stability is another key factor that determines the lifetime of the materials, which is rarely investigated for Mg3 Sb2- x Bi x . Here we show that Mg3 Sb2- x Bi x is more sensitive to moisture, but not to the conventionally considered oxygen. A spontaneous decomposition to crystalline Bi/Sb and amorphous Mg(OH)2 is thermodynamically favorable in the moist ambient air, leading to catastrophically degraded thermoelectric performance. Moreover, such an irreversible degradation was also found to occur in other Bi-contained Zintl phase compounds. Thankfully, if moisture is eliminated, the thermoelectric properties of Mg3 Sb2- x Bi x keep nearly unchanged after two months' exposure to the dry air. This work provides insight into the degradation mechanism of Mg3 Sb2- x Bi x and other Bi-contained thermoelectric materials, paving the way for their protection in future applications. Graphical Abstract: Graphical Abstract. Image, graphical abstract .